Analisa Perlindungan Hukum Terhadap Konsumen Pemalsuan Merek Produk Gula di Daerah Banyumas - Puji Lestari, Ismiyati Riri; Herning Sitabuana, Tundjung (Fakultas Hukum, Universitas Islam Balitar, 2023)
The growth of the goods and services industry provides positive impacts and alternative choices for consumers, but counterfeit products can threaten the health and cause long-term losses. This is due to the existence of business actors who seek profits by using shortcuts that aim to profit from the products they sell, trying to gain profits by unethical means, such as selling counterfeit products. This research aims to protect consumers from counterfeit products and examine legal efforts to make business actors responsible for losses. The results of the research using normative research methods show that business actors must be responsible for harming consumers, legal sanctions for fraudulent actors include imprisonment of up to 5 years or a fine of up to Rp 2 billion.